Project of a Permanent Observatory on Digital Editions of Italian authors (OPEDIt). First investigations on digitization practices and on the authoritativeness of the edition of Italian literary texts in electronic format - BOLOGNA (Prassi Ecdotiche della Modernità Letteraria, 2017)
The project of the Permanent Observatory on Digital Editions of Italian authors (OPEDIt) is presented, aimed at identifying guidelines for the online distribution of Classics of Italian literature, in order to monitor, regulate and make reliable also from a textual point of view. and scientific authoritativeness, the texts placed on the web and usable by a wide audience. The goal is to ensure that the methodology of traditional ecdotics is also taken into account in the case of digital editions present in the network.
Keywords: digital humanities; digital philology; digital edition